Aerobic Exercise Regulates Apoptosis through the PI3K/Akt/GSK-3β Signaling Pathway to Improve Cognitive Impairment in Alzheimer's Disease Mice. (10th September 2022) - Peng, Yan; Chi, Rui; Liu, Gang; Tian, Weijie; Zhang, Jun; Zhang, Rihui
Abstract : Neuronal apoptosis is an important factor in the etiology of Alzheimer's disease (AD). Aerobic exercise (AE) enhances learning and memory, improves cognitive impairment, increases telomere binding protein expression, and decreases apoptosis regulators, but it remains unclear whether it can improve cognitive impairment caused by neuronal apoptosis in AD. Therefore, this study investigated whether an 8-week running table exercise intervention could reduce apoptosis and improve cognitive function in the hippocampal neurons of AD model mice. After the exercise intervention, we evaluated the learning memory ability (positioning, navigation, and spatial search) of mice using a Morris water labyrinth, Nissl staining, immunohistochemistry, and protein application to detect hippocampal PI3K/Akt/GSK-3 β signaling pathway protein and hippocampal neuronal cell apoptosis protein B cell lymphoma 2 (Bcl-2) and apoptosis-promoting protein bcl-2-related X (Bax) protein expression. The results showed that aerobic exercise improved the location and spatial exploration ability of mice, increased the number of PI3K- and p-Akt-positive cells, increased the expression of PI3K, p-Akt, and bcl-2 proteins, decreased the expression of GSK-3 β and Bax proteins, and increased the bcl-2/Bax ratio of mice. The results suggest that aerobic exercise can reduce apoptosis and improve cognitive function in AD mice. The molecular mechanism may involve activation of the PI3K/Akt/GSK-3 β signaling pathway.